THE SHIFT FROM CONVENTIONAL MARKETING COMMUNICATIONS TO NEW MEDIA IN THE DIGITAL ERA - Iing Saefudin (Branding: Jurnal Manajemen dan Bisnis, 2025)
Changing consumer behavior, which is increasingly digital-centric, is forcing businesses to revamp their communication strategies to remain relevant and competitive. This study aims to analyze the shift in marketing communications from conventional to new media and identify the driving factors and their impact on the effectiveness of message delivery to consumers. The research employed a descriptive qualitative method through literature review and document analysis related to digital marketing trends. Secondary data collection was obtained from scientific journals, books, and the latest digital marketing industry reports. The results indicate that the transition to new media is driven by the advantages of interactivity, cost efficiency, the ability to precisely target audiences (hyper-targeting), and the accountability of real-time data measurement metrics. This strategic shift has implications for changing consumer behavior, leading to more independent, critical, and empowered consumers who base their trust on peer-to-peer reviews. However, marketers also face the challenges of information overload and the risk of an instant reputation crisis, which necessitate the implementation of a cross-channel (omnichannel) media convergence strategy. The shift to new media is not simply a replacement for physical media, but rather an essential transformation in modern business communications that demands the integration of sophisticated digital technology and authentic, transparent human relationships with consumers.